Two-Way Coupling Simulation of Solid-Liquid Two-Phase Flow and Wear Experiments in a Slurry Pump - Lei Jiang; Ling Bai; Peng Xue; Guangjie Peng; Ling Zhou (Journal of Marine Science and Engineering, 2022)
The slurry pump is one of the most important pieces of equipment in mineral transportation and separation systems, and it has complex two-phase flow characteristics and wear mechanisms. By employing numerical and experimental methods, the solid–liquid two-phase flow characteristics and wear patterns were investigated in this study. A two-way coupling discrete phase model (DPM) method was used to predict the flow pattern and the wear location and shows good agreement with the experimental observations. The pump performance characteristics of numerical results under pure water conditions were consistent with the experimental results. The effects of particle parameters and operating conditions on the internal flow field and wear were compared and discussed. The results show that the wear degree increased with the increase in volume flow rate and solid volume fraction. With the increase in particle size, the wear range at the impeller inlet became significantly smaller, but the wear degree became obviously larger. This study provides a basis for reducing the wear and improving the hydraulic performance of slurry pumps.